2022
DOI: 10.1155/2022/2081501
|View full text |Cite
|
Sign up to set email alerts
|

CircNRIP1 Exerts Oncogenic Functions in Papillary Thyroid Carcinoma by Sponging miR-653-5p and Regulating PBX3 Expression

Abstract: Background. Circular RNA circ_0004771 (termed circNRIP1) was identified by RNA-Seq previously and was elevated in papillary thyroid carcinoma (PTC) tissues. A series of studies also showed that circNRIP1 was upregulated in some tumors and could promote the malignant progression of tumors. This research intended to focus on the role of circNRIP1 in PTC progression and explore the mechanisms underlying circNRIP1 functions. Methods. RT-PCR or western blot determined circNRIP1, miR-653-5p, and pre-B-cell leukemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Meng et al identified that circ_PTK2 promoted EMT‐mediated tumor metastasis and gemcitabine resistance in bladder cancer via modulate PABPC1and SETDB1 expression 36 . Long‐standing evidence suggested that circ_NRIP1 acted as oncogenes in various cancers including cervical cancer, ovarian cancer, nasopharyngeal carcinoma, papillary thyroid carcinoma, osteosarcoma, and so on 37–41 . However, the specific roles of circ_NRIP1 in BTC remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meng et al identified that circ_PTK2 promoted EMT‐mediated tumor metastasis and gemcitabine resistance in bladder cancer via modulate PABPC1and SETDB1 expression 36 . Long‐standing evidence suggested that circ_NRIP1 acted as oncogenes in various cancers including cervical cancer, ovarian cancer, nasopharyngeal carcinoma, papillary thyroid carcinoma, osteosarcoma, and so on 37–41 . However, the specific roles of circ_NRIP1 in BTC remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…36 Long-standing evidence suggested that circ_NRIP1 acted as oncogenes in various cancers including cervical cancer, ovarian cancer, nasopharyngeal carcinoma, papillary thyroid carcinoma, osteosarcoma, and so on. [37][38][39][40][41] However, the specific roles of circ_NRIP1 in BTC remain unclear. Consequently, we decided to investigate whether circ_NRIP1 expedited BTC progression (Figure 8).…”
Section: Akt2 Was the Downstream Gene Of Mir-515-5pmentioning
confidence: 99%
“…As a circRNA encoded by COL1A1, previous studies have shown that circRNA_0044556 plays a vital role in the occurrence and development of tumors, including colorectal cancer [20,21], gastric cancer [22] and TNBC [12]. The in nite malignant proliferation of tumor cells and inhibition of apoptosis are the core factors in tumor development and change [23,24]. Therefore, we performed a series of experiments in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins regulate the mitochondrial outer membrane permeability and release apoptotic signaling proteins through multiple signaling pathways. In thyroid cancers, 10 circRNAs have been reported to inhibit cancer cell apoptosis via ceRNA mechanisms [ 60 68 ]. For instance, circ_0057209 upregulates STK4 by acting as a miR-183 sponge to activate the Hippo pathway.…”
Section: Circrnas and Their Roles In Regulating Tc Hallmarksmentioning
confidence: 99%